Post Pandemic Era – Adopting Tele-dentistry - Dikshit, Parajeeta (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Dentistry, the field of medicine where the communication sets standards for success. A continuous patient and dentist as well multidisciplinary dental communication leads to accuracy in diagnosis, increased efficiency as well as better patient satisfaction and long term positive outcomes. However the COVID-19 has brought a hindrance in the regular dental practice. The dental work demands a close proximity between the dentists with the patient which pitches them at a higher risk of being affected by the virus. Hence, international as well as national policy making associations and organizations have suggested only emergency and minimal aerosols generating treatment procedures. The dentists have almost been in hibernation, along with the waves of the pandemic and the constant lockdowns, carrying out free consultations for regular patients of their practices, through the phone and even chats. Can this be an opportunity to include tele-communication tools in routine dental practice?